Ten‐Eleven Translocation Family Proteins: Structure, Biological Functions, Diseases, and Targeted Therapy - Junzhi Liang; Xinni Na; Lingbo Meng; Lixia He; Ting Shu; Yuanyuan Fang; Bowen Zhang; Zhongyu Zhao; Cuishan Guo; Tingting Li; Zhijing Na; Da Li; et al. (MedComm, 2025)
ABSTRACT Ten‐eleven translocation (TET) family proteins are Fe(II)‐ and α‐ketoglutarate‐dependent dioxygenases, comprising three family members: TET1, TET2, and TET3. These enzymes drive DNA demethylation by sequentially oxidizing 5‐methylcytosine to 5‐hydroxymethylcytosine, 5‐formylcytosine, and 5‐carboxylcytosine. Through these reactions, TET proteins remodel the epigenetic landscape and interact with transcription factors and RNA polymerase II to regulate gene expression, cell lineage specification, and embryonic development. Mutations and dysregulation of TETs have been associated with the pathogenesis of various diseases, including the nervous system, immune system, and metabolic diseases, as well as cancers. Therapeutic modulation of TETs may be an effective strategy for the treatment of these diseases. Here, we provide a comprehensive overview of the mechanisms by which TET proteins mediate DNA demethylation and detail their biological functions. Additionally, we highlight recent advances in understanding the molecular mechanisms linking TET dysregulation to disease pathogenesis and explore their potential as therapeutic targets. This review supplements the current understanding of the critical role of epigenetic regulation in disease pathogenesis and further facilitates the rational design of targeted therapeutic agents for diseases associated with mutations and dysregulation of TETs.